1998
DOI: 10.2118/52503-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Gelation Behavior of a Polyacrylamide/Aluminum Citrate Colloidal-Dispersion Gel System

Abstract: This paper (SPE 52503) was revised for publication from paper SPE 37220, first presented at the 1997 SPE International Symposium on Oilfield Chemistry held in Houston, 18-21 February. Original manuscript received for review 18 February 1997. Received manuscript revised 27 June 1998. Revised manuscript approved 5 August 1998. Summary The gelation behavior of a polyacrylamide/aluminum citrate colloidal-dispersion gel (CDG) system was investigated in sandpacks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…Most studies have focused on propagation of gel in porous medium and finding ways to delay the gelation time. The gelation behavior of colloidal dispersion gel system was studied by Ranganathan et al (1998) and Rocha et al (1989) with the aim to understand the performance of CDG on in-depth permeability modification. Dong et al (1998) performed extensive displacement experiments and also studied CDG structure and rheology using atomic force microscopy (AFM) and dynamic rheological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on propagation of gel in porous medium and finding ways to delay the gelation time. The gelation behavior of colloidal dispersion gel system was studied by Ranganathan et al (1998) and Rocha et al (1989) with the aim to understand the performance of CDG on in-depth permeability modification. Dong et al (1998) performed extensive displacement experiments and also studied CDG structure and rheology using atomic force microscopy (AFM) and dynamic rheological methods.…”
Section: Introductionmentioning
confidence: 99%
“…[124][125][126][127][128]155,156 That is, they are NOT super-polymer flooding agents. In particular, researchers from the University of Kansas 125,126 , the University of TX 124 , and New Mexico Tech 156,157 found that resistance factors (effective viscosities) provided by aluminum-citrate-HPAM colloidal dispersion gels within cores (i.e., beyond the inlet core section) were the same as those provided by polymer solution alone (i.e., containing no crosslinker). This observation suggests that either the gel particles were too small to interact significantly with pore throats or the crosslinking reaction did not take place to a significant extent.…”
Section: Laboratory Results Many Previous Lab Tests Show No Effect Ofmentioning
confidence: 99%
“…If gelation is stopped sufficiently early or if gels are sufficiently sheared so that gel particles remain significantly smaller than pore throats, the gel suspensions can propagate through porous rock; however, the level of mobility reduction (residual resistance factor) is generally small (less than 2). 16 Independent studies at several locations (the University of Kansas, 125,126,155 the University of TX, 124 New Mexico Tech, 156,157 Stavanger College, 128 and BP 127 ) confirm that aluminum-citrate-HPAM gelants and gels behave like other gelants and gels.…”
Section: Are Colloidal Dispersion Gels Reallymentioning
confidence: 93%
See 2 more Smart Citations